Assessing the essentiality of the decaprenyl‐phospho‐d‐arabinofuranose pathway in Mycobacterium tuberculosis using conditional mutants. Issue 1 (7th March 2014) - Kolly, Gaëlle S.; Boldrin, Francesca; Sala, Claudia; Dhar, Neeraj; Hartkoorn, Ruben C.; Ventura, Marcello; Serafini, Agnese; McKinney, John D.; Manganelli, Riccardo; Cole, Stewart T.
Summary In Mycobacterium tuberculosis the decaprenyl‐phospho‐d‐arabinofuranose (DPA) pathway is a validated target for the drugs ethambutol and benzothiazinones. To identify other potential drug targets in the pathway, we generated conditional knock‐down mutants of each gene involved using the TET‐PIP OFF system. dprE1, dprE2, ubiA, prsA, rv2361c, tkt and rpiB were confirmed to be essential under non‐permissive conditions, whereas rv3807c was not required for survival. In the most vulnerable group, DprE1‐depleted cells died faster in vitro and intracellularly than those lacking UbiA and PrsA. Downregulation of DprE1 and UbiA resulted in similar phenotypes, namely swelling of the bacteria, cell wall damage and lysis as observed at the single cell level, by real time microscopy and electron microscopy. By contrast, depletion of PrsA led to cell elongation and implosion, which was suggestive of a more pleiotropic effect. Drug sensitivity assays with known DPA‐inhibitors supported the use of conditional knock‐down strains for target‐based whole‐cell screens. Together, our work provides strong evidence for the vulnerability of all but one of the enzymes in the DPA pathway and generates valuable tools for the identification of lead compounds targeting the different biosynthetic steps. PrsA, phosphoribosyl‐pyrophosphate synthetase, appears to be a particularly attractive new target for drug discovery.